Pop‐off data storage tags reveal niche partitioning between native and non‐native predators in a novel ecosystem. Issue 1 (29th October 2019) - Raby, Graham D.; Johnson, Timothy B.; Kessel, Steven T.; Stewart, Thomas J.; Fisk, Aaron T.
Abstract: Niche partitioning might be predicted to be particularly dynamic in 'novel ecosystems' characterized by human‐altered environmental conditions and biological invasions. Restoration efforts for native species in such systems can be informed by detailed characterization of niche partitioning. In Lake Ontario, fishery management agencies have been engaged in a long‐term struggle to restore native top predators including lake trout ( Salvelinus namaycush ). Meanwhile, management agencies continue to stock non‐native species like Chinook salmon ( Oncorhynchus tshawytscha ) into the lake to support a recreational fishery and to help control the abundance of a non‐native forage fish, the alewife ( Alosa pseudoharengus ). We used pop‐off data storage tags to study fine scale (9.1M lines of data from 22 animals) behaviour and habitat use by lake trout (native) and Chinook salmon (non‐native) in Lake Ontario in terms of depth and temperature, recorded at ≤70 s intervals for periods of up to 12 months. Chinook salmon occupied warmer and shallower waters during summer than did lake trout, and their niche breadth was wider. They achieved greater niche breadth in part because they were much more active vertically, cumulatively traveling 103 ± 1 m/hour during summer (model‐estimated median), whereas most lake trout were relatively inactive vertically (7 ± 1 m/hour). In each of our analyses, there was more inter‐individual variation among lake trout than among Chinook salmon, driven by some lake trout that spent considerable time making forays into warmer, shallower waters. Synthesis and applications . Our results illustrate the different foraging tactics used by two species in the Great Lakes and reflect their distinct life histories. Physical niche partitioning between Chinook salmon and lake trout helps to explain how these species can co‐exist in a multi‐species fishery even while having overlap in diet. The diversity of behaviours exhibited here by native lake trout have likely helped them persist during dramatic changes to the forage base in recent decades; that flexibility could help underlie their long‐term prospects for restoration during future changes to the ecosystem. Abstract : Top: A Chinook salmon in an onboard sampling trough with a pop‐off data storage tag (pDSTs) attached, ready for release back into Lake Ontario. Bottom: A lake trout equipped with a pDST being released over the stern of the fishing vessel after tagging. Photo credits: Natalie Sopinka.